Growth and Income Poverty in Latin America and the Caribbean: Evidence from Household Surveys - Leonardo Gasparini; Federico Gutiérrez; Leopoldo Tornarolli (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2005)
This paper provides evidence on growth and income poverty in Latin American and the Caribbean. Results are obtained by processing microdata from household surveys of 18 LAC countries covering the 1990s and early 2000s. Over this period the LAC economies have experienced very heterogeneous patterns of growth and poverty changes. Most countries in the region have had a rather meager performance in terms of poverty reduction. Episodes of positive, significant and unambiguously pro-poor income growth have been rare in Latin America in the last 15 years.
Keywords: D3; I32; O54; 330; poverty; growth; inequality; pro-poor growth; Latin America.